Formulation and Evaluation of Microsponge Based Nicorandil Sustained Released Tablet - Patel, S. S.; Patel, M. R.; Patel, M. J. (Journal of Scientific Research, 2017)
The aim of the present work was to develop once-daily sustained release microsponges formulations of Nicorandil, a potent potassium channel opener used in cardiovascular diseases and it has low oral bioavailability (70%) and half-life 1 h. So, it is good candidate for sustained release formulations based on microsponge technology. The microsponges were prepared by using quasi-emulsion solvent diffusion method. Scanning Electron Microscopy (SEM) revealed that the microsponges of nicorandil with Eudragit - RSPO and HPMC K100M were smooth, porous, glossy and discrete spherical. The actual drug content and encapsulation efficiency of batch M1 to M9 were obtained in range of 62.05 ± 0.31 to 80.69 ± 0.43 and 64.41 ± 1.71 to 70.58 ± 1.12, respectively. The microsponges formulations were subjected to in-vitro release studies and the results were evaluated kinetically and statically. The best fitted model was found to be Korsmeyer - Peppas model (R2 = 0.9992) for M6 batch. The n value for Korsmeyer - Peppas model was between 0.5 and 1.0 which is indicative of non-Fickian diffusion. Statistical analysis using ANOVA yielded a p value of 0.572 for all the formulations, indicating that there was no significant difference among them.